Impedance‐Enabled Camera‐Free Intrinsic Mechanical Cytometry (Small Methods 7/2022). Issue 7 (20th July 2022) - Feng, Yongxiang; Chai, Huichao; He, Weihua; Liang, Fei; Cheng, Zhen; Wang, Wenhui
Abstract : Back Cover In article number 2200325, Wang and coworkers present a camera‐free intrinsic mechanical cytometry (CFIMC) for high‐throughput single‐cell intrinsic mechanical characterization. The strategy of CFIMC adopts a framework that couples the impedance electrodes with the constriction channel spatially, so that the impedance signals contain the dynamic deformation of the cell squeezing through the constriction channel.